Inter-noise '96. The 25th International Conference on Noise Control July 30th through to August 2nd 1996 - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1995)
The conference is promoted by the Institute of Acoustics and organised under the superversion of. The International Institute of Noise Control Engineering. The theme for 96 is "Noise, the next 25 years — scientists engineers and legislators in partnership”.